2022
DOI: 10.3389/fphar.2022.1076351
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, distribution, and sustainability of traditional medicinal plants in Kaski district, western Nepal

Abstract: Medicinal plants are the primary source of traditional healthcare systems in many rural areas mostly in developing countries. This study aimed to document and analyze the diversity, distribution, and sustainability of the traditional medicinal plants used by the Gurung people of the Sikles region in western Nepal. Ethnobotanical data were collected through focus group discussions and individual interviews, and analyzed using descriptive and inferential statistics. Prior informed consent was obtained before eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 109 publications
2
1
0
Order By: Relevance
“…Torres-Avilez et al (2016) also did not find a significant difference between men and women in terms of their knowledge on traditional herbal medicine because these differences are not unidirectional and can only be detected on small scales of studies. A greater knowledge gap between both genders is not likely or improbable (Torres-Avilez et al, 2016;Khakurel et al, 2022). There have also been various reports of studies on ethnomedicinal knowledge and applications among Kenya's various communities consistent with the current study reporting a higher proportion of male participants than the females (Kimondo et al, 2015;Ochwang'i et al, 2014;Wanjohi et al, 2020b) and indeed other regional and international studies (Amjad et al, 2017;Faruque et al, 2018;Okori et al, 2022).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Torres-Avilez et al (2016) also did not find a significant difference between men and women in terms of their knowledge on traditional herbal medicine because these differences are not unidirectional and can only be detected on small scales of studies. A greater knowledge gap between both genders is not likely or improbable (Torres-Avilez et al, 2016;Khakurel et al, 2022). There have also been various reports of studies on ethnomedicinal knowledge and applications among Kenya's various communities consistent with the current study reporting a higher proportion of male participants than the females (Kimondo et al, 2015;Ochwang'i et al, 2014;Wanjohi et al, 2020b) and indeed other regional and international studies (Amjad et al, 2017;Faruque et al, 2018;Okori et al, 2022).…”
Section: Discussionsupporting
confidence: 83%
“…The older responders provided more information since they have access to a greater amount of the oral tradition knowledge passed down from generations before them (Miguéis et al, 2019;Dapar et al, 2020;Weldearegay and Awas, 2021). This outcome is based on a great deal of experience, indicating that knowledge on medicinal plants develops over a long period of time (Dapar et al, 2020;Khakurel et al, 2022). Where "Ip" is the number of informants who share their knowledge about a given species for the treatment of a specific disease and "Iu" is the total number of all informants who reported all uses about a given plant species.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicate no difference in the number of known medicinal species between genders, similar to what other studies have reported (Khakurel et al 2022, Pfeiffer & Buzts 2005. Men and women show significant differences in how they acquire knowledge and use plants significantly (Alqethami et al 2020).…”
Section: Does Gender Influence the Richness Of Medicinal Species?supporting
confidence: 92%